Pemahaman Perkembangan Kognitif Anak Sebagai Kunci Pembelajaran Yang Efektif - Handayani, Isna; Mustikaati, Wina; A, Anazah; Zakiyyan, Faza; Robiah, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the positive impact of cognitive understanding on the learning process of elementary school students. The background of this research is the crucial role of teachers in recognizing students’ cognitive development to ensure effective and meaningful learning. This study uses a literature review method by analyzing various relevant academic sources. The findings show that cognitive understanding helps students grasp learning materials more easily, supports classroom management, and improves learning outcomes. Therefore, cognitive aspects should be a key consideration in designing elementary-level learning strategies.